KAJIAN TEORI KONFLIK PEKERJAAN-KELUARGA DAN KEPUASAN KERJA: STUDI LITERATURE REVIEW - Ketut Juliartini; Ida Ayu Putri Laksmidewi Purba (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
Human resources are the company's most important asset. Even though the development of information technology is increasingly massive, the role of human resources cannot be replaced. This relates to management functions that must be carried out to ensure that the company's business activities run well according to the stated objectives. Therefore, companies are expected to not only focus on work results as a form of employee productivity, but also encourage employee job satisfaction. The greater the job satisfaction felt by employees, the greater their work productivity will be. There are various factors that can influence employee job satisfaction, such as providing financial and non-financial compensation. However, in its development, employee job satisfaction is not only influenced by the company side, but also by the individual employee's condition. Achieving job satisfaction is faced with various obstacles, one of which is related to work-family conflict felt by employees. Untreated work-family conflict can result in work stress and affect employee job satisfaction.